2013
DOI: 10.1088/1367-2630/15/9/093009
|View full text |Cite
|
Sign up to set email alerts
|

Spin–orbit-induced hole spin relaxation in InAs and GaAs quantum dots

Abstract: We study the effect of valence band spin-orbit interactions (SOI) on the acoustic phonon-assisted spin relaxation of holes confined in quantum dots (QDs). Heavy hole-light hole (hh-lh) mixing and all the spin-orbit terms arising from zinc-blende bulk inversion asymmetry (BIA) are considered on equal footing in a fully three-dimensional Hamiltonian. We show that hh-lh mixing and BIA have comparable contributions to the hole spin relaxation in self-assembled QDs, but BIA becomes dominant in gated QDs. Simultaneo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 54 publications
(192 reference statements)
1
36
0
Order By: Relevance
“…The period of the anisotropic leakage is critically dependent on the relative magnitude of Zeeman interaction terms linear and cubic in the magnetic field. The current and singlet-triplet exchange splitting can be effectively adjusted by an appropriate choice of field direction, providing a simple control variable for quantum information processing and a way of tailoring magnetic interactions in hole spin qubits.Spin-based quantum information processing platforms relying on hole quantum dots (QDs) have recently attracted considerable attention [1][2][3][4][5][6][7][8][9][10][11], since they permit long spin coherence and electrically driven spin resonance thanks to the strong hole spinorbit (SO) interaction [12][13][14][15][16][17][18][19][20]. Owing to their effective spin J = 3 2 , spin dynamics in hole systems often exhibits physics not found in electron systems [21][22][23][24][25][26].…”
mentioning
confidence: 99%
“…The period of the anisotropic leakage is critically dependent on the relative magnitude of Zeeman interaction terms linear and cubic in the magnetic field. The current and singlet-triplet exchange splitting can be effectively adjusted by an appropriate choice of field direction, providing a simple control variable for quantum information processing and a way of tailoring magnetic interactions in hole spin qubits.Spin-based quantum information processing platforms relying on hole quantum dots (QDs) have recently attracted considerable attention [1][2][3][4][5][6][7][8][9][10][11], since they permit long spin coherence and electrically driven spin resonance thanks to the strong hole spinorbit (SO) interaction [12][13][14][15][16][17][18][19][20]. Owing to their effective spin J = 3 2 , spin dynamics in hole systems often exhibits physics not found in electron systems [21][22][23][24][25][26].…”
mentioning
confidence: 99%
“…The complete expressions and derivation of the piezoelectric potential and the deformation potential operators for the three phonon branches is presented in [31]. The transition rate between the initial hole state |Ψ h i and the final hole state |Ψ h f is estimated using the Fermi golden rule…”
Section: Theoretical Modelmentioning
confidence: 99%
“…[28] Several works have theoretically addressed the hole spin relaxation in single QDs taking into account different SOI mechanisms and have showed that one or another prevail depending on the QD traits. [20,29,30,31,32] By comparison, the spin relaxation of holes in DQDs is still poorly understood. This is inspite of their promising prospects for the development of quantum information architectures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 and 15, which is confirmed here using exact numerical solutions of the three-dimensional system. [27][28][29] To understand the different magnitude of the gaps, note that D s 2 takes place at F $ 0, while D s 1 does so at F ( 0 (see the example in Fig. 1(b)).…”
mentioning
confidence: 99%